A new species of Myrmecotypus Pickard-Cambridge spider (araneae: corinnidae: castianeirinae) from the Bolivian orocline, imitating one of the world's most aggressive ants - Perger, Robert (2021)
A new species of ant-mimicking spider of the subfamily Castianeirinae, Myrmecotypus rubrofemoratus Perger and Rubio, new species (Araneae: Corinnidae), is described from the Pre-Andean area of the Bolivian orocline. Adults of M. rubrofemoratus new species resemble the carpenter ant Camponotus femoratus Forel, 1907, which is considered one of the most aggressive ants in the world.